Implementasi Layanan Pengarsipan Administrasi Keuangan Lapak-Peng Berbasis Whatsapp pada BPKK Aceh Jaya - Maulidar Maulidar; Adria Adria; Herliani Herliani; Banta Diman; Dimas Bagus Susanto; Rina Novi Yani (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
This study was motivated by the need for a more efficient, fast, and adaptive financial administrative archiving system in government institutions. The Regional Financial Management Agency (BPKK) Aceh Jaya faced challenges in managing financial administrative documents, particularly in document distribution processes that were previously conducted manually, thereby reducing the effectiveness of internal coordination. As an innovative effort, BPKK Aceh Jaya implemented the WhatsApp-based Financial Administrative Archiving Service (LAPAK-Peng). This study aims to analyze the implementation of LAPAK-Peng using George C. Edward III’s policy implementation theory, which includes communication, resources, disposition, and bureaucratic structure. This study employed a descriptive qualitative approach, with data collected through in-depth interviews with five informants, observation, and documentation. Data were analyzed using the Miles and Huberman interactive model, with validity tested through source and technique triangulation. The findings indicate that LAPAK-Peng supports the effectiveness of financial administration at BPKK Aceh Jaya, with communication emerging as the most dominant factor due to its role in accelerating coordination and information exchange. In addition, successful implementation was supported by adequate resources, positive implementer disposition, and a clear bureaucratic structure. This study concludes that WhatsApp can serve as an alternative digital administrative innovation to support document management in government institutions.